2021
DOI: 10.1371/journal.ppat.1008807
|View full text |Cite
|
Sign up to set email alerts
|

The human cytomegalovirus protein UL147A downregulates the most prevalent MICA allele: MICA*008, to evade NK cell-mediated killing

Abstract: Natural killer (NK) cells are innate immune lymphocytes capable of killing target cells without prior sensitization. One pivotal activating NK receptor is NKG2D, which binds a family of eight ligands, including the major histocompatibility complex (MHC) class I-related chain A (MICA). Human cytomegalovirus (HCMV) is a ubiquitous betaherpesvirus causing morbidity and mortality in immunosuppressed patients and congenitally infected infants. HCMV encodes multiple antagonists of NK cell activation, including many … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…US3 (66)) (reviewed in (71)). Indeed, although US9 is capable of reducing MICA*008 surface expression in isolation, a HCMV deletion mutant lacking US9 is still capable of reducing MICA*008 surface levels (48) consistent with the recent definition of pUL147A as an additional HCMV encoded immunevasin targeting MICA*008 (47).…”
Section: The Hcmv Us9 Gene Product Plays a Role In Suppressing Cell S...supporting
confidence: 79%
See 2 more Smart Citations
“…US3 (66)) (reviewed in (71)). Indeed, although US9 is capable of reducing MICA*008 surface expression in isolation, a HCMV deletion mutant lacking US9 is still capable of reducing MICA*008 surface levels (48) consistent with the recent definition of pUL147A as an additional HCMV encoded immunevasin targeting MICA*008 (47).…”
Section: The Hcmv Us9 Gene Product Plays a Role In Suppressing Cell S...supporting
confidence: 79%
“…This is unsurprising given that HCMV encodes a number of functional proteins to target the same pathway e.g. MICA (44,45,47,48), MHC I (71), FcgR activation (83). We predict that HCMV encodes additional gene product(s) to target MR1 that will be a focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NK cells are an important component of the innate immune system to fight against HCMV infection. Studies have found multiple genetic loci (e.g., UL16 and UL142; UL = unique long) in the HCMV genome, and their transcripts inhibit NK cell recognition [30]. Natural killer Group 2 member D (NKG2D) belongs to the C-type lectin-like activating re-ceptor family that is expressed ubiquitously on all NK cells to mediate immune surveillance on virus-infected cells after binding with NKG2D ligands (NKG2DLs).…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…The mutant’s surface expression was significantly decreased compared to wild type MICB. In addition, MRC-5 human lung fibroblasts were targeted for killing by NK cells when expressing a mutation in the UL147a gene [ 102 ].…”
Section: Immune Cell Responsesmentioning
confidence: 99%